ASSESSMENT OF PSYCHOSOCIAL ROLE FOR EPILEPTIC PATIENT WITH VAGUS NERVE STIMULATOR IMPLANTATION (Journal of Forensic Medicine & Toxicology, 2024)
Background: Vagus nerve stimulation (VNS) is a  non-pharmacological treatment of refractory epilepsy,  which also has an antidepressive effect. The favorable  combinations of VNS with specific mechanisms of action  of antiseizure medication (ASM) on mood and health related quality of life (HrQol)Objectives: This study aim to explore of psychosocial  role for epileptic patient with vagus nerve stimulator  implantation. Methodology: Institution-based cross-sectional study  design was conducted on 100 epileptic patients using  a non-probability sampling technique. Tis study was  conducted in two randomly selected hospitals of Baghdad  zones from December 18,2023 to January 20, 2024. All  epileptic patients on treatment follow up at selected public  hospitals of Baghdad City was the source population and  the sampled epileptic patients was the study population.  The data were collected using the WHO-QOL-SF36  questionnaire. The data were coded, cleaned and entered  into SPSS version 26.0. for analysis. Descriptive statistics  were expressed in frequency, percentage, mean and  standard deviation. Simple linear regression Pearson  correlation test was used to find an association between  dependent variable and each independent variable.
Keywords: Assessment; Psychosocial role; Epileptic patient; Vagus Nerve Stimulator Implantation